A phase 1b clinical trial to determine the safety, tolerability and immunogenicity of simian adenovirus and poxvirus vectored vaccines against Mycobacterium avium complex subspecies in patients with active Crohn’s diseaseResearch in context - Jeremy Sanderson; Jeremy Aboagye; Rebecca Makinson; Katerina Rapi; Samuel Provstgaard-Morys; Lisa Stockdale; Alison Lawrie; Isabelle Lanigan; Nishat Halim; Abdel Douiri; Emily Greenlay; Rayka Malek; et al. (EBioMedicine)
Summary: Background: Crohn’s Disease (CD) is a chronic, debilitating condition hypothesised to be associated with Mycobacterium avium ssp paratuberculosis (MAP) infection. It is the causative pathogen of the granulomatous inflammatory enteritis in ruminants, Johne’s Disease. A developing treatment approach is utilising heterologous prime-boost viral vectored vaccines. We report a Phase 1b dose-escalation trial to determine the safety, tolerability and immunogenicity of candidate recombinant ChAdOx2 and MVA vectored vaccines against MAP in patients with CD. Methods: 28 patients with mild to moderate CD, aged 18–50, were randomly allocated into 5 groups. Group 1 and 2 were vaccinated with ChAdOx2 HAV, Groups 3 and 4 with MVA HAV and Group 5 with both vaccines in a prime-boost regimen. A 112-day follow-up period assessed safety and tolerability by recording adverse events (AEs) and serious adverse events (SAEs). Secondary objectives of immunogenicity were assessed by ELISpot (enzyme-linked immunosorbent spot) and clinical response by Crohn’s Disease Activity Index (CDAI) and Simple Endoscopic Score for Crohn’s Disease (SES-CD). Findings: 28 participants received either a single dose of ChAdOx2 HAV (n = 12), a single dose of MVA HAV (n = 6) or a prime dose of ChAdOx2 HAV (n = 10) followed by an MVA HAV (n = 9) boost. Solicited AEs were 196 in all participants, one AE was graded as severe but resolved within 24 h. The majority of solicited AEs were graded as mild (149/196; 76%, 95% CI 69%–82%) or moderate (45/196; 23%, 95% CI 17%–29%). ELISpot responses increased in Groups 1 and 2 and significantly more after boosting with MVA HAV. Interpretation: Candidate vaccines ChAdOx2 HAV and MVA HAV were safe, well-tolerated and immunogenic in patients with active CD. A heterologous prime-boost schedule induces a T cell-mediated immune response. Further studies are required to determine the efficacy and optimal regime of the vaccines. Funding: HAV Vaccines Limited funded the trial and acted as trial sponsor. The Sponsor was involved in protocol development, trial conduct, including data monitoring and analysis, and the preparation of this manuscript in line with the Medicines for Human Use (Clinical Trials) Regulations 2004 and amendments.